Predictors of Medical Students’ Views toward Research: Insights from a Cross-Cultural Study among Portuguese-Speaking Countries - Correia, Gustavo; Pereira, Margarida; Gomes, Andreia; Bragança, Maria Do Rosário; Weber, Silke [UNESP]; Ferreira, Maria Amélia; Ribeiro, Laura (MDPI, 2022)
Developing the skills and interest in scientific research of medical students is crucial to ensuring effective healthcare systems. As such, in this study, we aimed to assess Portuguese-speaking medical students’ attitudes and perceptions toward scientific research and clinical practice, and how they are influenced by individual characteristics and regional indicators. A total of 455 first-year students from three medical schools in three countries (Portugal, Brazil, and Angola) participated in this study by completing a questionnaire. Portuguese students attributed the most importance to scientific skills and were the most confident in their ability to perform these skills. Angolan students were the most motivated to perform research and integrate it into the curriculum, despite having the most negative attitudes and perceiving themselves as having less ability to perform scientific skills. Brazilian students had the least positive attitudes toward science. In Portugal, attitudes depended on gross domestic product (GDP), while in Angola, they were influenced by the type of secondary school attendance. Portuguese students’ perceptions of scientific skills were related to sex, GDP, type of secondary school, and participation in research. In Brazilian and Angolan students, perceptions were associated with age and research participation, respectively. The findings support the need to promote skills and positive attitudes toward scientific research in future physicians, fostering physician-scientists and improving patient care.
Keywords: Cross-cultural study; Evidence-based medicine; Medical students; Physician-scientists; Undergraduate research